Intraindividual Variability in Executive Function Performance in Healthy Adults: Cross-Sectional Analysis of the NAB Executive Functions Module - Buczylowska, Dorota; Petermann, Franz (Frontiers in Psychology, 2018)
The current study was aimed at investigating across-tasks intraindividual variability, also termed dispersion, in EF performance. The German adaptation of the Neuropsychological Assessment Battery (NAB) was used as a measure of EFs. Data of 444 participants aged 18-99 from six NAB Executive Functions Module subtests (i.e., Planning, Mazes, Letter Fluency, Judgment, Categories, and Word Generation) along with the NAB Total Index score as a measure of overall cognitive ability were analyzed. Maximum discrepancy (MD) was applied as a measure of dispersion. MD values ranged from 0.47 to 5.20 indicating substantial across-tasks dispersion in EF performance. Furthermore, dispersion moderately decreased with advancing age. Taking overall cognitive ability into account revealed that dispersion might be lower at older ages; especially, when associated with low overall ability levels. The dedifferentiation hypothesis offers a plausible explanation for these findings. That is, the cognitive profiles of older people might be less heterogenous than that of younger people, which may be due to age-related central nervous system constraints.